Artikulasi Kebijakan Nasional dalam Konteks Lokalitas: Analisis Implementatif Program Merdeka Belajar Kampus Merdeka pada Perguruan Tinggi di Kota Bima - Firmansyah Firmansyah (Indonesian Journal Publisher, 2024)
This study aims to critically examine the dynamics of the implementation of the Merdeka Belajar Kampus Merdeka (MBKM) policy within higher education institutions in Kota Bima, with particular emphasis on the interplay between national policy design and the adaptive capacity of local institutions in peripheral contexts. The study employs a descriptive qualitative approach with an exploratory strategy, utilizing data collection techniques including field observations, in-depth interviews with institutional actors (leaders, lecturers, and students), and institutional document analysis. The data were subsequently analyzed through systematic coding, categorization, and thematic interpretation to identify patterns of implementation and policy distortions. The findings reveal that the implementation of MBKM does not follow a linear trajectory; rather, it is characterized by processes of negotiation, reinterpretation, and contextual adaptation shaped by constraints in human resources, digital infrastructure, partnership networks, and students’ economic capacity. These conditions have stimulated the emergence of institutional improvisation practices grounded in community-based initiatives and local collaborations, while simultaneously indicating disparities in access and the prevalence of administrative evaluation bias. Consequently, policy implementation is better understood as a complex interaction between policy structures, local institutional capacities, and the dynamics of educational inequality.